Edukasi Manajemen Pola Hidup Sehat di Desa Pegagan Julu, Kabupaten Dairi - Pipin Sumantrie; Martalina Limbong (Universitas Muhammadiyah Semarang, 2022)
The success of a country can be seen from the results of the Human Achievement Index (IPM) owned by the country. One indicator of HDI is health status. This community service has the aim of increasing people's motivation to maintain education on healthy lifestyles. In carrying out this community service, the method used in this community service activity is to conduct interactive health seminars, so that the expected materials and objectives can reach the community directly. The conclusions obtained from this activity are as follows, overall (100%) the people of Pegagan Julu IV village feel the benefits of the healthy lifestyle education activities that are delivered, but in their commitment to living a healthy lifestyle there are only 90% of the people who are committed to maintaining health, through a healthy lifestyle.